Science Homework for Key Stage 2 : Activity-based Learning. - Forster, Colin (Active homework., 2009)
Science Homework for Key Stage 2 is a unique resource for busy teachers - a selection of?pencil-free?, hands-on activities, aligned with the National Curriculum Programmes of Study.